2004
DOI: 10.4321/s1130-01082004000900005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and factors influencing on Helicobacter pylori infection recurrence

Abstract: Objectives: a) to determine the rate of H. pylori reinfection after successful eradication in a 4-year follow-up study; and b) to evaluate the contribution of different factors in the infection relapse.Patients and methods: a total of 208 patients (age range 18-81 years; average 50 years; 87 women) who had been successfully treated for H. pylori infection were included. Annually, urea breath test was assessed to determine H. pylori status after eradication. Age, sex, rural/urban environment, smoking habit, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…which found that risk of reinfection amongst children under 5 years old was 26 times higher than that amongst older individuals. Likewise, some studies have observed that the average age of reinfected patients is lower than that of patients who remain H. pylori negative, 23–26 although other studies performed in children could not confirm that the risk of reinfection depends on age 27 . The reason for this relationship between lower age and H. pylori recurrence is unknown, nor is it known whether it is due to differences in the distribution of other risk factors among age groups.…”
Section: Discussionmentioning
confidence: 97%
“…which found that risk of reinfection amongst children under 5 years old was 26 times higher than that amongst older individuals. Likewise, some studies have observed that the average age of reinfected patients is lower than that of patients who remain H. pylori negative, 23–26 although other studies performed in children could not confirm that the risk of reinfection depends on age 27 . The reason for this relationship between lower age and H. pylori recurrence is unknown, nor is it known whether it is due to differences in the distribution of other risk factors among age groups.…”
Section: Discussionmentioning
confidence: 97%
“…Limited information exists regarding risk factors for reinfection of H. pylori . Candidate risk factors include younger age [ 26 , 27 ], infection of close contacts [ 14 , 28 ], dental plaque [ 29 , 30 ], and contaminated endoscopic equipment [ 14 , 16 , 31 ]. Other studies did not identify any factors predictive of H. pylori reinfection [ 32 - 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, limited information exists regarding risk factors for reinfection of H. pylori . Some factors have been proposed as risk factor for reinfection, such as younger age , infection of close contacts , dental plaque , and contaminated endoscopic equipment . One report suggested that past history of peptic ulcer disease or identification of ulcer at the time of esophagogastroduodenoscopy was risk factor associated with reinfection .…”
Section: Discussionmentioning
confidence: 99%